Role of topical spironolactone in the treatment of acne: A systematic review of clinical trials—Does this therapy open a path towards favorable outcomes?. Issue 2 (22nd November 2022) - Rehan, Syeda Tayyaba; Khan, Zayeema; Abbas, Samina; Imran, Laiba; Munir, Saqib; Tahir, Muhammad Junaid; Kheljee, Aqib Zaman; Eljack, Mohammed Mahmmoud Fadelallah; Ahmed, Ali
Abstract: Acne vulgaris is the eighth most common disease worldwide and presents with inflammatory and noninflammatory skin lesions along with other dermal abnormalities. Oral spironolactone is used for treating acne vulgaris due to its antiandrogenic properties and inhibition of sebogenesis. Recent evidence shows that spironolactone in topical form has similar efficacy to its oral form with comparatively fewer adverse events associated with its use. However, to establish an evidence‐based understanding, this systematic review aims to investigate the efficacy and safety of topical spironolactone in the treatment of acne vulgaris. PubMed, ClinicalTrials.gov, Cochrane library, and Google Scholar were comprehensively searched from the date of inception till March 18, 2022 All the clinical trials experimenting with the role of topical spironolactone in the treatment of acne were included. Articles examining the effects of oral spironolactone or other topical agents were excluded. The Cochrane risk of bias assessment tool (RoB 2.0, version 2019) was used to assess the risk of bias in each study. The study findings have been reported in line with PRISMA 2020 guidelines. The literature search yielded 600 articles. Five clinical trials with 195 patients were included in this review. Out of the five trials, two showed a high risk of bias while three had overall some concerns. Patients treated with topical spironolactone showed a significant decrease in the number of papules ( p  = 0.004), closed comedones ( p  < 0.05), and lesions ( p  < 0.05). Compared to placebo, treatment with 5% spironolactone showed a significant decrease in total lesion count ( p  = 0.007). In addition, 2% spironolactone showed efficacy over clindamycin and reduced the number of comedones ( p  < 0.0001), papules ( p  < 0.0001), and pustules ( p  < 0.0001) while the acne severity index was also considerably lowered ( p  < 0.0001). Spironolactone was not found to affect significant skin hydration, sebum, elasticity, melanin, and redness ( p  > 0.05). Topical spironolactone yields better results than other first‐line treatments for acne and displays fewer side effects. However, further large‐scale clinical trials are required before spironolactone can be used as the preferred treatment in the clinical management of acne.